Big data management capabilities in the hospitality sector: Service innovation and customer generated online quality ratings. (August 2021) - Shamim, Saqib; Yang, Yumei; Zia, Najam Ul; Shah, Mahmood Hussain
Abstract: Despite the wide usage of big data in tourism and the hospitality sector, little research has been done to understand the role of organizations' capability of managing big data in value creation. This study bridges this gap by investigating how big data management capabilities lead to service innovation and high online quality ratings. Instead of treating big data management as a whole, we access big data management capabilities at the strategic and operational level. Using a sample of 202 hotels in Pakistan, we collected the primary data for big data capabilities, knowledge creation and service innovation; the secondary data about quality rating were collected from Booking.com . Structural equation modelling through SmartPLS was used for data analysis. The results indicated that big data management capabilities lead to high online quality ratings through the mediation of knowledge creation and service innovation. We contribute to the current literature by empirically testing how strategic level big data capabilities enable the firm to add value in innovativeness and positive online quality ratings through acquiring, contextualizing, experimenting and applying big data. Highlights: This study examines. The relationship between strategic and operational level big data management capabilities. The role of strategic and operational level capabilities on knowledge creation. The relationship of knowledge creation through big data and service innovation. Interplay of service innovation, knowledge creation and online quality ratings.